2020
DOI: 10.1177/0022487120949842
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Educator Technology Integration Preparation Practices Around TPACK in the United States

Abstract: Given the strong influence of teachers educators’ pedagogical modeling on new teachers’ capacity to use technology to support student learning, this study sought to answer two interrelated questions: (a) How are teacher educators and teacher education programs currently working to prepare teachers to integrate technology? and (b) How are teacher educators implementing the TPACK (complex integration of technological [T], pedagogical [P], and content [C] knowledge [K]) model? The evidence to answer these questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 50 publications
2
31
0
1
Order By: Relevance
“…Teachers need initial and ongoing training that is designed according to a series of principles that have been shown to be effective by educational research [ 53 ]: (1) orientation to curricular content; (2) use of active learning strategies; (3) involvement of teachers in collaboration; (4) use of models and/or modelling; (5) facilitation of coaching and expert support; (6) availability of time for feedback and reflection; and (7) sustained medium- and long-term duration. Voithofer & Nelson [ 54 ] investigated how teacher trainers implement the TPACK model [ 55 ], that is, the complex integration of curricular, pedagogical and technological knowledge into their training programs. The results of this study showed that the adoption of the TPACK was quite limited and consequently, an adequate training model for the integral development of digital teaching competence is not being applied.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers need initial and ongoing training that is designed according to a series of principles that have been shown to be effective by educational research [ 53 ]: (1) orientation to curricular content; (2) use of active learning strategies; (3) involvement of teachers in collaboration; (4) use of models and/or modelling; (5) facilitation of coaching and expert support; (6) availability of time for feedback and reflection; and (7) sustained medium- and long-term duration. Voithofer & Nelson [ 54 ] investigated how teacher trainers implement the TPACK model [ 55 ], that is, the complex integration of curricular, pedagogical and technological knowledge into their training programs. The results of this study showed that the adoption of the TPACK was quite limited and consequently, an adequate training model for the integral development of digital teaching competence is not being applied.…”
Section: Discussionmentioning
confidence: 99%
“…28 A recent study shows that while technology is being rapidly incorporated in teacher education, the level of adoption and teachers' conceptions around technology varies greatly. 29 In addition, Dietrich and colleagues 30 indicate a need to acknowledge high school teachers' working conditions in which required equipment may be unavailable and internet connection speed may be limited. Some teachers' lack of familiarity with recent technology may also explain why PD programs that offer opportunities of modeling technology in the context of specific instructional approaches, such as the one conducted by Bell and colleagues, 31 are perceived to be beneficial.…”
Section: Reducing Cognitive Loadmentioning
confidence: 99%
“…Previous research has indicated that teaching and learning with unfamiliar technologies can be problematic . A recent study shows that while technology is being rapidly incorporated in teacher education, the level of adoption and teachers’ conceptions around technology varies greatly . In addition, Dietrich and colleagues indicate a need to acknowledge high school teachers’ working conditions in which required equipment may be unavailable and internet connection speed may be limited.…”
Section: Pivoting From Face-to-face To Remote Deliverymentioning
confidence: 99%
“…In these studies, the lack of direct influences of TCK and TPK suggests that preparing teachers to integrate technology is more than simply developing their isolated technology skills. Furthermore, the teachers' access of technology does not equate to effective teaching, nor does it affirm that teachers will utilize the technology to enhance teacher capacity or support student learning (Voithofer and Nelson, 2020). The integration of technology must be intentional and purposeful, focused on student learning and acquisition of knowledge.…”
Section: Remote Lesson Study and Digital Technologymentioning
confidence: 99%